The potential of rice husk ash for silica synthesis as a semiconductor material for monocrystalline solar cell: a review. Issue 1 (April 2021) - Putranto, A W; Abida, S H; Sholeh, A B; Azfa, H T
Abstract: The solar cell is a device that can convert solar energy into electrical energy. The solar cell is promising energy because it is environmentally friendly compared to fossil fuel. The essential component in the solar cells is silicon. Silicon is a semiconductor that can absorb sunlight. However, the available solar cells currently have relatively high prices since the semiconductor compiler material requires many processes and expensive. Rice husk ash can be used as a producer of environmentally friendly silicon at affordable prices. The rice husk could produce 87-97% silica and 16-25% ash. In general, the silica content of rice husk ash is 94-96%. The processes for producing silica material as a semiconductor were, such as rice husk ash preparation, greying, leaching, making silicon by reduction, and conductivity test. This review aimed to provide insight into converting the rice husk ash to solar cells.